2019
DOI: 10.1071/en19026
|View full text |Cite
|
Sign up to set email alerts
|

On the potential of on-line free-surface constructed wetlands for attenuating pesticide losses from agricultural land to surface waters

Abstract: Environmental contextPesticide losses from land to surface waters have the potential to cause ecological damage. Furthermore, pesticides in surface waters present a major challenge for water companies accessing these waters for the domestic supply, in terms of complying with water quality regulations. Here, we evaluate the potential of field- and ditch-scale free-surface constructed wetland systems for reducing pesticide transfers from land to surface waters. AbstractPesticides make important contributions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In fact, other studies reported limited mass removal in wetlands with comparable residence times. Ramos et al (2019) did not find relevant R M in two surface flow wetlands, with residence times between 45 min and 6 h in England. In contrast, Passeport et al (2013) found R M between 45 % and 96 % in a constructed wetland with a residence time of 66.5 h. However, their contaminant mass loss coincided with loss of water (45 %).…”
Section: Contaminant Mass Removalmentioning
confidence: 65%
See 1 more Smart Citation
“…In fact, other studies reported limited mass removal in wetlands with comparable residence times. Ramos et al (2019) did not find relevant R M in two surface flow wetlands, with residence times between 45 min and 6 h in England. In contrast, Passeport et al (2013) found R M between 45 % and 96 % in a constructed wetland with a residence time of 66.5 h. However, their contaminant mass loss coincided with loss of water (45 %).…”
Section: Contaminant Mass Removalmentioning
confidence: 65%
“…Such systems temporally retain polluted waters and thus provide space, time, and favorable conditions for degradation processes. VTSs studied in literature include very different types of systems (Lange et al, 2011), including vegetated ditches or detention ponds with hydraulic residence times (HRT) ranging in the order of minutes to several hours (Bundschuh et al, 2016;Elsaesser et al, 2011;Ramos et al, 2019) or constructed wetlands in which HRT may reach several weeks (Maillard and Imfeld, 2014), particularly when operated in batch mode (Tournebize et al, 2017;Maillard et al, 2016;Moore et al, 2000). The term "pesticide mitigation" can refer to contaminant mass removal (R M ) or peak concentration reduction (R C ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of CWs in eliminating nitrogen and phosphorous, the selection of plants, and CW monitoring that uses multiple models are all research themes in this cluster. For example, the potential of two freesurface CW systems to reduce pesticide concentrations in surface water was evaluated by combining in-field monitoring and dynamic fugacity modelling [67]. Recently, research on CWs has focused on complex agroecosystems [68], and nitrogen and phosphorus removal is no longer a frontier or hot spot.…”
mentioning
confidence: 99%
“…Our assumption is that all the arable land in the catchment is under-drained. Details of the monitoring set up, sampling protocol and analytical methods employed are given in 14 Where possible, samples were analysed within a week of sample collection. In this case, samples were kept in the dark at 4°C before analysis.…”
Section: Monitoringmentioning
confidence: 99%